2014
DOI: 10.4103/0301-4738.126990
|View full text |Cite
|
Sign up to set email alerts
|

Comparing measurement techniques of accommodative amplitudes

Abstract: Aim and Background:This study was designed to compare four standard procedures, for determining the monocular accommodative amplitudes.Materials and Methods:Fifty-two students participated in this analytical-descriptive study. Accommodative amplitudes were measured using four common clinical techniques, namely: Push-up, push-down, minus lens, and modified push-up.Results:The highest amplitude was obtained using the push-up method (11.21 ± 1.85 D), while the minus lens technique gave the lowest finding (9.31 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 23 publications
0
30
1
Order By: Relevance
“…7,40,41 AA was measured by the minus lens method, as it is the one with the best repeatability. 42,43 Relative accommodation evaluates the patient's ability to increase and decrease accommodation in conditions where the demand for total vergence is constant. That is, it determines the maximum variations of accommodation stimulus that can be effected in near vision, maintaining optotype vision clear.…”
Section: Measurementsmentioning
confidence: 99%
“…7,40,41 AA was measured by the minus lens method, as it is the one with the best repeatability. 42,43 Relative accommodation evaluates the patient's ability to increase and decrease accommodation in conditions where the demand for total vergence is constant. That is, it determines the maximum variations of accommodation stimulus that can be effected in near vision, maintaining optotype vision clear.…”
Section: Measurementsmentioning
confidence: 99%
“…Other studies have also found a strong correlation between the two push-up methods. 10,15,16 Differences in methodology make direct comparisons with other studies difficult, yet the methodology of this study most closely resembles that of Chen and O'Leary. 15 This study found results that were further away from the participant (higher mean near point of accommodation measurements) for the conventional push-up method (8. 15 for the different push-up methods.…”
Section: Discussionmentioning
confidence: 94%
“…Conventional push-up measurements were found to be closer to the participant (lower measurement (cm)) compared with the modified PAGE 37 OF 39 :: 39 PAGES push-up method, which is comparable to the findings of several other studies. 10,[12][13][14][15][16] Although the results from the two methods were significantly different statistically, clinically the difference was small as the conventional push-up method produced results that were, on average, 0.73 cm closer to the participant than the modified method. When comparing right eye, left eye and binocular measurements, the difference was still low (right eye: 0.51 cm, left eye: 0.61 cm, both eyes open: 1.05 cm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Monocular amplitude of accommodation was evaluated by averaging the values of two push-up and two push-down trials, to compensate for the bias of push-up to overestimate and push down to underestimate accommodation amplitude. 26 Accommodative responses were recorded in the dominant eye (the contralateral eye was occluded with an eye patch) for a period of at least 5 seconds for each of the previously described 60 configurations randomly presented. All conditions were measured in one session that took approximately 45 minutes, including breaks.…”
Section: Examination Protocolmentioning
confidence: 99%